Analysis of factors affecting Murabaha Financing with third party funds as a moderating variable - Arfionita, Asyifa Nur; Sa'adati, Nila (Islamic Accounting Journal, 2023)
The purpose of this study was to determine the results of the analysis of the effect of Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Operational Expenses on Operating Income (BOPO) on Murabahah Financing with Third Party Funds (DPK) as Moderating Variables in Islamic Commercial Banks. 2016-2020 period. This research is a quantitative research using secondary data obtained from the financial statements of each bank on their official website. By using 12 samples of Islamic commercial banks in the 2016-2020 period. The test results show that BOPO has a positive and significant effect on murabahah financing. Meanwhile, FDR and CAR have no effect on murabahah financing. And based on the results of the MRA test, it shows that DPK is not able to moderate the effect of FDR, CAR, BOPO on murabahah financing.